Phenolic characterization of olive genotypes potentially resistant to Xylella. Issue 1 (31st December 2022) - Vergine, Marzia; Pavan, Stefano; Negro, Carmine; Nicolì, Francesca; Greco, Davide; Sabella, Erika; Aprile, Alessio; Ricciardi, Luigi; De Bellis, Luigi; Luvisi, Andrea
ABSTRACT: The outbreak of the olive quick decline syndrome caused by Xylella fastidiosa represents one of the main agricultural threats in Italy. Recently, thirty asymptomatic or paucisymptomatic genotypes found in olive groves heavily compromised by the bacterium were identified. HPLC ESI/MS-TOF analyses on leaf petiole extract were carried out to characterize the metabolic profile of selected genotypes. Besides uni- and multi-variate statistical methods differentiated the metabolic profiles of olive genotypes genetically related to the cultivars 'Leccino' and 'Ciciulara', no common metabolic pattern was found among the selected genotypes with respect to susceptible one. In-depth evaluation of seven selected phenolic compounds highlighted quantitative differences between genotypes and the susceptible control cultivar but a resistance-related pattern cannot be yet defind. Nevertheless, an unusually high concentration of quercetin-3-O-rhamnoside characterized a genotype genetically related to Tunisian cultivars which displayed no symptoms besides high bacterial concentration, suggesting how tolerance may be related to peculiar phenolic profiles.